Minimal mutational requirements for conversion of a telomere resolvase into a Cre-like site-specific recombinase - Shu Hui Huang; Kerri Kobryn (PLoS ONE, 2026)
Hairpin telomere resolvases comprise a family of enzymes that produce the hairpin (hp) telomeres of bacteria and their phages that possess linear chromosomes and plasmids terminated by covalently closed hp telomeres. The hp telomeres overcome the dual issues of end replication and protection faced by all organisms with linear genomes. The hp telomeres are produced from replicated intermediates in which the hp telomeres have been converted into replicated telomere ( rTel ) junctions possessing inverted repeat symmetry. The telomere resolvases process the rTel junctions in a reaction with mechanistic similarities to that promoted by type IB topoisomerases and tyrosine recombinases. The telomere resolvase of both Borrelia burgdorferi (ResT) and Agrobacterium tumefaciens (TelA) have been shown to be able to promote, under certain conditions, a Cre-like recombination between rTel junctions to produce the Holliday junction (HJ) intermediate typical of recombination reactions promoted by tyrosine recombinases. For TelA mutation of the enzyme was required to unmask this normally cryptic activity. A complex combination of autoinhibition domain deletion and point mutation of TelA had even been shown to completely switch the activity of TelA from a telomere resolvase to a recombinase. We report here that mutation of a pair of aspartic acid residues in TelA is sufficient to accomplish this switch in activity.